Correlation Between HbA1C Levels And C-Reactive Protein Levels In Diabetes Mellitus Patients - TIMBUL MUJIONO; DITA PRATIWI KUSUMA WARDANI; ARIF MULYANTO; MINTO RAHAJU (Jurnal Ilmiah Kesehatan)
Diabetes mellitus (DM) is a chronic disease characterised by elevated blood glucose levels ≥ 200 mg/dl due to metabolic disorders. Insulin resistance triggers a blood glucose imbalance, resulting in no energy supply needed by the body's cells. The condition of DM is destructive to the body and, therefore, needs to be measured with stable parameters for the long term. HbA1c is a standard clinical examination used as a determinant of glycaemic status in DM disease. C-reactive protein (CRP) level is an effective parameter in determining the index of damage or inflammation that occurs in the body due to DM. This study aims to determine the relationship between HbA1c levels and CRP levels in patients with diabetes mellitus at Dr. Sardjito Hospital. Twenty patients with type 2 diabetes mellitus were included in this study using the purposive sampling technique. HbA1c data and CRP levels were analysed with the Spearman correlation test. The Pearson correlation test results showed a p-value = 0.001 and an r-value = 0.705. There is a relationship between HbA1c levels and CRP levels in DM patients at RSUD Dr. Soedirman Kebumen.